Widening the applications of the Just-Dip-It approach: a solid contact screen-printed ion-selective electrode for the real-time assessment of pharmaceutical dissolution testing in comparison to off-line HPLC analysis. Issue 22 (9th April 2021) - Kelani, Khadiga M.; Badran, Osama M.; Rezk, Mamdouh R.; Elghobashy, Mohamed R.; Eid, Sherif M.
Abstract : For the widening of Just-Dip-It approach, screen-printed ion-selective electrodes were used for providing real-time monitoring of the time-dependent chemical processes during dissolution testing. This is advantageous over the traditional HPLC method. Abstract : Over past years, the field of pharmaceutical dissolution testing has significantly expanded to cover not only the quality control of dosage forms, but also to play an important role in the bioavailability testing paradigm and screening of most formulations. These tests usually need a very long time sampling and monitoring, so that the automation of sampling is laborsaving. Problems often occur with these automatic devices due to sampling lines that may disconnect, crimp, carry over, become mixed up, or are inadequately cleaned. Potentiometric sensors, such as liquid contact (LC-ISE) or solid contact ion-selective electrodes (SC-SP-ISE), can provide timely data to be used for the real-time tracking of the amount of active pharmaceutical ingredients (APIs) released in the dissolution medium without these problems. In this work, we adopted the Just-Dip-It approach as a process analytical technology solution with the ultimate goal of advancing the ion selective sensors to their most effective use in pharmaceutical analysis. Two sensors were fabricated, the traditional LC-ISE and SC-SP-ISE. The sensing poly-vinyl chloride membranes of two electrodes were prepared using 2-nitrophenyl octyl ether as a plasticizer to soften the membrane, and the reduction in resistance to pioglitazone ions (PIO) permeability was achieved through the incorporation of sodium tetraphenylborate and calix[8]arene as a cationic exchanger salt and inclusion complexing ligand, respectively. Finally, prepared membranes were turned into the flexible perm-selective slices of hydrophobic plastic, which work as a barrier to other compounds, except for the PIO cation in the concentration range of 1 × 10 −6 to 1 × 10 −2 M and 1 × 10 −5 to 1 × 10 −2 M for SC-SP-ISE and LC-ISE, respectively. The challenges and opportunities of both sensors in comparison to a developed HPLC method were discussed for the dissolution testing of the combination dosage forms of pioglitazone. Potentiometric methods were validated according to IUPAC guidelines, while HPLC was validated according to ICH guidelines to ensure accuracy and precision.